Thyroid Autoimmunity and Function after Treatment with Biological Antirheumatic Agents in Rheumatoid Arthritis - Bliddal, Sofie; Borresen, Stina Willemoes; Feldt-Rasmussen, Ulla (Frontiers in Endocrinology, 2017)
With the increased pro-inflammatory response in both rheumatoid arthritis and thyroid autoimmune diseases, treatment with biological antirheumatic agents of the former may affect the course of the latter. In hepatitis C and cancer patients, treatment with biological agents substantially increases the risk of developing thyroid autoimmunity. As the use of biological antirheumatic agents in the treatment of rheumatoid arthritis is increasing, this review aimed to investigate if such use affected thyroid status in rheumatoid arthritis patients. We conducted a systematic literature search and included six studies with a total of 311 patients as well as three case reports. The patients were treated with tumor necrosis factor-α inhibitors (infliximab, etanercept or adalimumab) or the monoclonal CD20-antibody rituximab. There was a non-significant trend of slight improvement of both thyroid function and autoantibody-status: a reduction of thyroid peroxidase- and thyroglobulin antibody concentrations, and a reduction of thyrotropin levels in hypothyroid patients. Despite the small number of studies, they presented compliant data. The biological antirheumatic agents used in rheumatoid arthritis thus did not seem to negatively affect thyroid status in patients with rheumatoid arthritis, and can be considered safe with regard to thyroid autoimmunity. However, the well-established association between rheumatic diseases and thyroid autoimmunity necessitates continued monitoring of thyroid function in patients with rheumatoid arthritis. Each new biological antirheumatic agent should be scrutinized for its effect on thyroid as well as other autoimmunity in order to establish concise recommendations for patient follow-up for each agent and each disease.